The Association Between Depressive Symptomology, Psychological Burden Related to COVID-19, and Engagement in Physical Exercise Among College Students - Vally, Zahir; Helmy, Mai (Frontiers in Psychiatry, 2021)
Introduction: The coronavirus (COVID-19) pandemic has resulted in substantial changes to the normalcy of daily life. Research conducted in Western Europe point to elevated levels of depression, rumination and worry as well psychological burden. These in turn impact the capacity of individuals to adhere to lockdown measures and health-protective behaviours Investigations of these pandemic-related mental health constructs in the Middle East appears sparse. Moreover, there is an immense need to investigate the potential for simple strategies that might be used by individuals whilst in lockdown to combat the onset of mental health difficulties. Regular physical exercise may prove valuable in this regard. Method: A sample of 1322 participants (mage = 19.50 years, SD = 1.54) completed measures of depression and psychological burden related to COVID-19 and self-reported their frequency of physical exercise. Data were collected between February and May 2021 in Egypt and the United Arab Emirates. Results: Analyses revealed statistically significant associations between depression and psychological burden as well as between elevated depression and reduced physical exercise. Mediation analyses in which the potential mediational role of physical exercise was examined were not significant. Conclusions: Depression and psychological burden related to the pandemic appear to be prevalent in these Middle Eastern locations. Whilst physical exercise appears to be beneficial in combating depression, it does not appear to be a sufficient strategy for impeding the experience of psychological burden. Investigation of the contribution of additional strategies is required.